Optimalisasi Proteksi Tanaman Padi melalui Perancangan Alat Pengusir Burung Otomatis Berbasis Arduino ATmega2560 dan Solar Panel - Heri Tri Irawan; Rahmat Satya; Roid Alazhar Nasution; Iing Pamungkas (Jurnal Optimalisasi, 2026)
Bird pests such as sparrows, weavers, munias, and finches pose a serious problem for rice farmers, particularly during the generative growth stage when ripening panicles are easily consumed, causing yield losses of up to 30–50% and threatening food security. Traditional deterrent methods, including scarecrows, noise-making devices, and firecrackers, provide only temporary effects with limited coverage and require repetitive manual supervision that is both exhausting and inefficient. This study aims to design and develop an automatic bird repellent device based on sensors and a microcontroller, powered by an independent solar panel system, to protect rice crops effectively without continuous human monitoring. The research adopts a stepwise prototype development approach consisting of planning (designing a steel-pipe frame and selecting components such as an Arduino ATmega2560, HC-SR04 ultrasonic sensor, PIR sensor, tweeter speaker, 50 Wp solar panel, and 12 V 8 Ah battery), production (hardware assembly and Arduino C programming), testing (sensor–sound functionality and field operation), and performance evaluation through analysis of detection data and reduction in bird attacks. The results show that the device operates stably, with PIR detection up to 11 m, ultrasonic detection from 1–4 m, audiosonic output at 4069 Hz (84–91 dB), an effective repulsion radius of 14 m, and a reduction in bird attacks of about 90% (from 100 events to 3 events over six days), all using stand-alone solar energy without significant disturbances. The system is environmentally friendly, weather-resistant, and has the potential to improve rice farming productivity, with further recommendations including optimization of sensor positioning and enhanced protection against extreme weather conditions.